A sub-specialised emergency general surgery on call can improve theatre utilisation - Musbahi, Aya; Abdulhannan, Peshang; Rao, Milind; Gopinath, Bussa (International Surgery Journal, 2019)
Background: Theatre efficiency and delivery of a safe emergency general surgery service are important topics in the current climate of limited funding and resources. No studies have examined the impact of restructuring a general surgery emergency on call system on theatre utilisation and efficiency. Methods: Data was collected for twelve months prior and twelve months after the introduction of a sub-specialised on call system on operating minutes, out of hours operating and which procedures were done after 10 PM using a prospectively maintained database. Theatre utilisation was calculated and compared using a paired T test. Results: In 2012, between 8 AM and 5 PM, 993 emergency procedures were done in 2012 compared 1300 in 2015 corresponding to 34585 and 90311 minutes of operating respectively and 17.5% and 45.8% of total theatre time available (p<0.05). 160 procedures in 2012 were performed after 10 PM and 106 in 2015 corresponding to 16457 and 9341 minutes respectively (p<0.0001). Conclusions: A sub-specialised emergency general surgery on call system can improve theatre utilisation.